Large‐Scale Production of Bismuth Chalcogenide and Graphene Heterostructure and Its Application for Flexible Broadband Photodetector. (16th March 2016) - Song, Jingchao; Yuan, Jian; Xia, Fang; Liu, Jingying; Zhang, Yupeng; Zhong, Yu Lin; Zheng, Jialu; Liu, Yan; Li, Shaojuan; Zhao, Meng; Tian, Zhiming; Caruso, Rachel A.; et al.
Abstract : Large‐scale production of 2D van der Waals heterostructures with precisely controlled chemical composition is the major challenge hindering their practical electric and optoelectronic applications. In this work, a solvothermal method is demonstrated to produce van der Waals heterostructures consisting of metal chalcogenides and graphene in a large scale. In situ powder X‐ray diffraction reveals that graphene plays an important role as atomic template to grow bismuth chalcogenide nanoplatelets with preferential stoichiometry of Bi2 Se1.5 Te1.5, which is naturally unstable. It is found that Bi2 Se1.5 Te1.5 has the minimum lattice mismatch with graphene (<0.1%). The release of lattice mismatch strain between Bi2 Se1.5 Te1.5 and graphene sheet is evidenced by a new peak in the ultraviolet photoelectron spectroscopy. A macroscale free‐standing heterostructured thin film with excellent mechanical flexibility is fabricated by simply filtering the large‐scale solution processed heterostructure. The heterostructure film is used to fabricate a flexible photodetector, which shows a broadband photo response and excellent durability in a bending test. The heterostructure material and device demonstrated in this work may shed light to flexible optoelectronic devices and applications. Abstract : A solvothermal method is employed for large‐scale production of Bi2 Se1.5 Te1.5 ‐graphene van der Waals heterostructures. With minimum lattice mismatch and enhanced interlayer interaction in this heterostructure, as‐produced free‐standing heterostructure film shows improved electrical, photoelectric, and mechanical properties, making it a promising photoresponsive material for flexible photodetector.